In Vitro Antifungal Evaluation of Seven Different Disinfectants on Acrylic Resins. (5th June 2014) - Yildirim-Bicer, A. Z.; Peker, I.; Akca, G.; Celik, I.
Abstract : Objective . The aim of this study was to evaluate alternative methods for the disinfection of denture-based materials. Material and Methods . Two different denture-based materials were included in the study. Before microbial test, the surface roughness of the acrylic resins was evaluated. Then, the specimens were divided into 8 experimental groups ( n = 10 ), according to microorganism considered and disinfection methods used. The specimens were contaminated in vitro by standardized suspensions of Candida albicans ATCC#90028 and Candida albicans oral isolate. The following test agents were tested: sodium hypochlorite (NaOCl 1%), microwave (MW) energy, ultraviolet (UV) light, mouthwash containing propolis (MCP), Corega Tabs, 50% and 100% white vinegar. After the disinfection procedure, the number of remaining microbial cells was evaluated in CFU/mL. Kruskal-Wallis, ANOVA, and Dunn's test were used for multiple comparisons. Mann Whitney U test was used to compare the surface roughness. Results . Statistically significant difference ( P < 0.05 ) was found between autopolymerised and heat-cured acrylic resins. The autopolymerised acrylic resin surfaces were rougher than surfaces of heat-cured acrylic resin. The most effective disinfection method was 100% white vinegar for tested microorganisms and both acrylic resins. Conclusion . This study showed that white vinegar 100% was the most effective method for tested microorganisms. This agent is cost-effective and easy to access and thus may be appropriate for household use.